2021
DOI: 10.1002/cpp.2591
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of borderline personality disorder and bipolar disorder: Self‐concept, identity and self‐esteem

Abstract: Symptoms of borderline personality disorder (BPD) and bipolar disorder (BD) often overlap. In some cases, it is difficult to conduct a differential diagnosis based only on current diagnostic criteria Therefore, it is important to find clinical factors with high discriminatory specificity that, used together with structured or semi‐structured interviews, could help improve diagnostic practice. We propose that a clinical analysis of identity, self‐concept and self‐esteem may help distinguish the two disorders, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 141 publications
(181 reference statements)
0
1
0
Order By: Relevance
“…No research could be found on variations in the self-experience during the crisis in manic episodes. More precisely, there is a range of compatible topics that are approximate but do not cover the issue, for example, personality and identity in bipolar disorder, belief system, goal pursuit and self-concept (Ironside et al, 2019;Inder et al, 2008;Fulford et al, 2008;Wright et al, 2022).…”
Section: Early Mentions Key Features and Patterns Of Current Studies:...mentioning
confidence: 99%
“…No research could be found on variations in the self-experience during the crisis in manic episodes. More precisely, there is a range of compatible topics that are approximate but do not cover the issue, for example, personality and identity in bipolar disorder, belief system, goal pursuit and self-concept (Ironside et al, 2019;Inder et al, 2008;Fulford et al, 2008;Wright et al, 2022).…”
Section: Early Mentions Key Features and Patterns Of Current Studies:...mentioning
confidence: 99%